2013
DOI: 10.1038/ncomms3910
|View full text |Cite
|
Sign up to set email alerts
|

The smooth muscle-selective RhoGAP GRAF3 is a critical regulator of vascular tone and hypertension

Abstract: Although hypertension is a worldwide health issue, an incomplete understanding of its etiology has hindered our ability to treat this complex disease. Here we identify arhgap42 (also known as GRAF3) as a Rho-specific GAP expressed specifically in smooth muscle cells in mice and humans. We show that GRAF3-deficient mice exhibit significant hypertension and increased pressor responses to angiotensin II and endothelin-1; these effects are prevented by treatment with the Rho-kinase inhibitor, Y-27632. RhoA activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(78 citation statements)
references
References 28 publications
(36 reference statements)
3
73
0
1
Order By: Relevance
“…We have previously shown that the Rho-specific GTPase-activating protein ARHGAP42 is highly and selectively expressed in SMCs and that global gene-trap-mediated reduction in ARHGAP42 levels resulted in hypertension (11). By characterizing the transcription mechanisms that control human ARHGAP42 expression, we have now identified a novel mechanism for the BP-associated locus within the ARHGAP42 first intron.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…We have previously shown that the Rho-specific GTPase-activating protein ARHGAP42 is highly and selectively expressed in SMCs and that global gene-trap-mediated reduction in ARHGAP42 levels resulted in hypertension (11). By characterizing the transcription mechanisms that control human ARHGAP42 expression, we have now identified a novel mechanism for the BP-associated locus within the ARHGAP42 first intron.…”
Section: Discussionmentioning
confidence: 94%
“…In brief, thoracic aortae were stripped of endothelial and adventitial layers by microdissection, and then SMCs were dispersed by treatment with trypsin and collagenase. Cells were maintained in DMEM supplemented with F12 and 10% FBS and used from passages [5][6][7][8][9][10][11][12][13][14][15]. SMC preparations are routinely tested for smooth muscle differentiation marker gene expression, and only those that are deemed at least 85% pure by these measurements are used for further experimentation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ARHGAP42 (also known as GRAF3) is a GTPase‐activating protein 12. Rho family small GTPases regulate cellular functions, including diverse cytoskeleton‐related events, gene transcription, and immune cell migration and inflammation 13.…”
Section: Introductionmentioning
confidence: 99%
“…The Rho GTPase‐activating proteins (Rho‐GAPs) are one of the most important types of regulators of Rho GTPases 16. A previous study has identified ARHGAP42 as a Rho‐specific GAP expressed specifically in smooth muscle cells (SMCs) in mice and humans 12. The study has indicated that ARHGAP42‐mediated inhibition of RhoA activity in vascular SMCs is necessary to maintain normal blood pressure homeostasis.…”
Section: Introductionmentioning
confidence: 99%